The revaluation of previously discovered reserves under the modern economical conditions - A. A. Mautina; I. V. Popov (Известия высших учебных заведений: Геология и разведка, 2015)
The necessity of conducting the geological and economic revaluation of previously discovered reserves under the modern conditions for the mainienance and development of mineral resource base of the country is justified. Nickel and cobalt deposits are shown as an example how changing the values of the techno-economic parameters in time can affect the indexes of the performance of the deposit. Geological-economic estimation of reserves will help to clarify the status of mineral resource base in today’s dynamic market conditions of mineral raw materials, which affect the indexes of the efficiency of the field development.